The value of plasma omega-3 polyunsaturated fatty acids in predicting the response and prognosis of cervical squamous cell carcinoma patients to concurrent chemoradiotherapy - Ping, Pengbin; Li, Juan; Xu, Xiaoying (Frontiers in Pharmacology, 2024)
In recent years, abnormalities in plasma omega-3 polyunsaturated fatty acids (omega-3 PUFAs) have been proven to be related to the risk of cancer, but their prognostic value for cancer is unclear. The purpose of this study was to retrospectively evaluate the response and prognostic significance of plasma omega-3 PUFAs in patients with cervical squamous cell carcinoma (CSCC) treated with concurrent chemoradiotherapy (CCRT). Spearman rank correlation analysis was used to analyze the correlation between omega-3 PUFAs and squamous cell carcinoma antigen (SCC-Ag) levels. Methods: A total of 89 patients with CSCC who underwent CCRT were evaluated retrospectively. Binary logistic regression analysis was used to analyze the independent predictors related to complete response (CR) after CCRT. A Cox proportional hazard model and Kaplan-Meier analysis were utilized to perform survival analysis. Results: According to multivariate logistic regression analyses, a high level of plasma EPA was independently correlated with an increased incidence of CR after CCRT (odds ratio (OR), 0.980; 95% confidence interval (CI), 0.962-0.999, P=0.038). With a median follow-up of 41.3 months, the CSCC patients in the high EPA (≥46.0 nmol/mL) group exhibited longer OS and PFS. According to our multivariate analysis, pretreatment plasma EPA level was an independent prognostic factor for PFS in patients with CSCC who underwent CCRT (hazard ratio (HR), 0.263; 95% CI, 0.089-0.782, P=0.016). However, it was not an independent prognostic factor of OS. Spearman rank correlation analysis revealed was a negative correlation between pretreatment SCC-Ag (pre SCC-Ag) levels and EPA levels (r =-0.305, P=0.004), and a weak negative correlation between posttreatment SCC-Ag (post SCC-Ag) levels and EPA levels (r =-0.251, P=0.018). Conclusion: Plasma omega-3 PUFAs are related to the response and survival outcome of patients with CSCC who underwent CCRT. Pretreatment plasma EPA levels may be a promising biomarker for predicting the response and prognosis of patients with CSCC who undergo CCRT. In addition, the pretreatment plasma EPA levels presented a negative correlation with the SCC-Ag levels